Seasonal variation of Sargassum ilicifolium (Phaeophyceae) growth on equatorial coral reefs. Issue 2 (29th January 2019) - Low, Jeffrey K. Y.; Fong, Jenny; Todd, Peter A.; Chou, Loke Ming; Bauman, Andrew G.
Abstract : Temporal and spatial variations in Sargassum ilicifolium thallus density and length were investigated on equatorial coral reefs in Singapore from November 2011 to October 2012. Thalli density varied little throughout the year, however, we found strong seasonal patterns in thallus length and identified temperature as the significant driver. Sargassum ilicifolium reached maximum length in December (110.39 ± 2.37 cm) during periods of cooler water temperatures, and minimum length in May (9.88 ± 0.48 cm) during periods of warmer water temperatures. Significant spatial variation was also observed for both thallus density and length of S. ilicifolium among reefs. Within reefs, densities of S. ilicifolium were higher on reef flats (20.40 ± 0.40 individuals · 0.25 m −2 ) compared to upper reef slopes (5.66 ± 0.23 individuals · 0.25 m −2 ). Our findings highlight that marked seasonality in the growth of canopy‐forming macroalgae can occur within equatorial reef systems where temperature ranges are restricted (<3°C).